Cranial fluctuating asymmetry and its relationship with non-specific physiological stress indicators in a contemporary South African cadaveric skeletal sample - (:unkn) unknown (My University, 2024)
ObjectivesBiological anthropologists frequently explore skeletal asymmetry, together with population health and disease. Given the conflicting findings in existing literature, this study aimed to clarify whether an association exists in a South African sample.MaterialsDry bone and cranial micro-focus X-ray Computed Tomography (micro-XCT) scans of 115 South African individuals were assessed.MethodsFluctuating asymmetry (FA) indices were calculated from interlandmark distances, and the frequency of four types of non-specific signs of physiological stress were documented to explore the relationship between FA and disease.ResultsBlack South Africans did not exhibit a high FA index; however, they had the highest prevalence of non-specific signs of physiological stress. However, no significant correlations were detected between FA indices and pathological lesions.ConclusionNo correlation was observed between FA and populations from different socio-economic backgrounds. However, individuals of lower socio-economic status (SES) demonstrated a greater prevalence of non-specific signs of physiological stress.SignificanceThis research suggests that skeletal indicators of stress may be a suitable biological marker for assessing differences in SES among population groups, while indicating that levels of cranial FA is an inadequate biological marker.LimitationsPossible limitations may include measurement error, and the lack of information on the life history and medical records of individuals in this sample.Suggestions for further researchFuture research should include a larger sample with more South African groups, and should evaluate the potential association among age, FA, and expression of skeletal markers of disease.
Keywords: African Research